Application of Redlich-Kister Model to Measure and Predict Thermo Physical Properties of Binary Liquid Mixtures at Various Temperatures - R., Ramesh; K., Ramesh; K., Yusoh (Penerbit Universiti Malaysia Pahang, 2014)
Study conducts in this research are Viscosities,ƞ,and densities, of 1, 4-dioxane with Benzene at different mole fractions and various temperatures in the atmospheric pressure condition. From experimentations excess volume, Vᴱ, and deviation sin viscosities ∆ƞ, of mixtures at infinite dilutions have been obtained.